Assessment of methods for estimation of effective atomic numbers of common human organ and tissue substitutes: waxes, plastics and polymers. Issue 2 (23rd May 2014) - Singh, V. P.; Badiger, N.M.; Kucuk, N.
Abstract : We calculated mass attenuation coefficients, effective atomic numbers and Kerma relative to air for human organ and tissue substitutes ( i . e . wax, plastic and polymer materials). The effective atomic numbers of the tissue substitutes were calculated by the direct method, interpolation method, Auto-Zeff software and single value XMuDat program and then compared. The calculated effective atomic numbers were also compared with available experimental data and a good agreement was observed. A large difference in effective atomic numbers calculated by the direct and interpolation methods was observed in photoelectric and pair-production regions. The direct method was found to be appropriate for effective atomic number computation in low-(>10 keV) and medium-(0.1 ≤ E ≤ 10 MeV) photon energy regions. Kerma relative to air of the selected tissue substitutes was found to be dependent upon the atomic number and element compositions, which show a sharp peak due to K-edge absorption.